2017
DOI: 10.1111/1468-4446.12346
|View full text |Cite
|
Sign up to set email alerts
|

Agency in advanced liberal services: grounding sociological knowledge in homeless people's accounts

Abstract: This paper aims to understand how people who are homeless respond to advanced liberal social services that endeavour to promote their autonomy and responsible actions. We prioritize the experiences and positions of people who are homeless, and what agentic action means to them. Sociological literature is selective about what accounts are deemed agentic. Agency is associated with accounts that resist or subvert dominant neoliberal framings of homelessness as failure of individuals. When people experiencing home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
1
26
0
1
Order By: Relevance
“…The stigma of being homeless works as a little story that connects to bigger stories of ‘appropriate behaviour’ of both citizens (active) and clients (passive). Consequently, there is no such thing as shelter residents’ absolutely rejecting or completely embracing the identities made relevant by today’s service model (Parsell and Clarke : 3). For instance, in two interview studies with homeless service administrators (Wasserman and Clair ) and representatives in a housing agency (Schneider ), it was shown that homeless people do not necessarily get a particular service simply by claiming it; instead they need to match specific service criteria (Wasserman and Clair ).…”
Section: Related Empirical Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The stigma of being homeless works as a little story that connects to bigger stories of ‘appropriate behaviour’ of both citizens (active) and clients (passive). Consequently, there is no such thing as shelter residents’ absolutely rejecting or completely embracing the identities made relevant by today’s service model (Parsell and Clarke : 3). For instance, in two interview studies with homeless service administrators (Wasserman and Clair ) and representatives in a housing agency (Schneider ), it was shown that homeless people do not necessarily get a particular service simply by claiming it; instead they need to match specific service criteria (Wasserman and Clair ).…”
Section: Related Empirical Studiesmentioning
confidence: 99%
“…Staff either ‘(1) subtly assist the clients in telling their stories, (2) focus on establishing the veracity of their accounts, (3) confront their stories as “irrational,” or (4) dismiss client narratives as of no institutional interest/importance (i.e., institutionally inappropriate)’ (Marvasti : 649). Alongside research on the agency of homeless people (Parsell and Clarke ), research on types of homeless ‘talk’ (Carr ; Gowan ), the storytelling of homeless people (Snow and Anderson ) and staff approaches to the homeless person’s narrative (Marvasti ) has inspired our approach. We expand his research by examining the agency involved in real time co‐constructions of clientship in placement meetings and by examining these ‘little stories’ in relation to the ‘bigger story’ of appropriate behaviour of clients and citizens.…”
Section: Related Empirical Studiesmentioning
confidence: 99%
See 3 more Smart Citations